2019
DOI: 10.1111/jvs.12783
|View full text |Cite|
|
Sign up to set email alerts
|

Summer precipitation limits plant species richness but not overall productivity in a temperate mesic old‐field meadow

Abstract: Question Water availability is a primary regulator of plant productivity and species richness in arid and semi‐arid ecosystems, but its influence in other habitats is much less clear partly because experimental manipulations of water are relatively rare. How important is soil moisture availability relative to other key environmental factors in determining plant species biomass and diversity in temperate mesic grasslands? Location An old‐field meadow in southeastern Ontario, Canada. Methods We established a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…effects on plant cover. The reduced plant cover under late-season drought also agrees with previous reports of decreased plant biomass and cover under summer (Perez-Camacho et al, 2012;Kreyling et al, 2017;Wagg et al, 2017;Serafini et al, 2019) and autumn drought (Nogueira et al, 2017). Decreased plant cover was mainly caused by the lower PF and SS cover (Figure 4b,c).…”
Section: Effects Of Late-season Drought On Plant Species Richness And...supporting
confidence: 90%
See 1 more Smart Citation
“…effects on plant cover. The reduced plant cover under late-season drought also agrees with previous reports of decreased plant biomass and cover under summer (Perez-Camacho et al, 2012;Kreyling et al, 2017;Wagg et al, 2017;Serafini et al, 2019) and autumn drought (Nogueira et al, 2017). Decreased plant cover was mainly caused by the lower PF and SS cover (Figure 4b,c).…”
Section: Effects Of Late-season Drought On Plant Species Richness And...supporting
confidence: 90%
“…Precipitation in the late growing season is critical for maintaining plant growth and biomass allocation. For example, summer drought can suppress plant species richness and plant growth by reducing soil water availability (Wagg et al, 2017; Stampfli et al, 2018; Serafini et al, 2019). Changes in drought timing do not affect all species equally, and can disproportionately affect particular plant species/functional groups due to the differences in life history and functional traits (Nippert & Knapp, 2007; Robertson et al, 2010; Báez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The csv files and R file have been deposited in Figshare, https://figshare.com/s/d2933788bc55814b47f3 ( 64 ). Previously published data were used for this work ( 8 , 27 , 34 , 43 , 44 , 53 , 65 …”
Section: Data Availabilitymentioning
confidence: 99%
“…However, much research has suggested that increasing precipitation increases species richness (Serafini, Grogan, & Aarssen, 2019;Yang et al, 2011). Our result could be explained by the following: First, soil moisture is relatively abundant during the growing season in alpine meadows on the Tibetan Plateau (Wang, Lan, & Jin, 1993).…”
Section: Direct and Indirect Effects Of Map And Mat On Alpine Meadomentioning
confidence: 75%
“…We also found that an increase in MAP indirectly decreased the species richness of the soil seed banks by directly decreasing the species richness of the aboveground plant communities. However, much research has suggested that increasing precipitation increases species richness (Serafini, Grogan, & Aarssen, 2019; Yang et al., 2011). Our result could be explained by the following: First, soil moisture is relatively abundant during the growing season in alpine meadows on the Tibetan Plateau (Wang, Lan, & Jin, 1993).…”
Section: Discussionmentioning
confidence: 99%